2021
DOI: 10.1097/mpg.0000000000003211
|View full text |Cite
|
Sign up to set email alerts
|

High Seroconversion Rate Against Severe Acute Respiratory Syndrome Coronavirus 2 in Symptomatic Pediatric Inflammatory Bowel Disease Patients

Abstract: Understanding coronavirus disease 2019 in pediatric inflammatory bowel disease (PIBD) is important. We describe a single-center cohort of COVID-19 PIBD patients where seroconversion against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was examined.Immunosuppressed PIBD patients at Texas Children's Hospital who tested positive for SARS-CoV-2 by nasopharyngeal reverse transcriptase polymerase chain reaction were included in the study. The clinical course of IBD, concurrent medications, COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…These results are in agreement with the observation that immunocompromised adult IBD patients with COVID-19 can develop a serologic response comparable to that of age-matched healthy controls ( 45 ). They are also in line with a recent study reporting a high rate of seroconversion (85%) in immunocompromised PIBD patients ( n = 12, median age 10 years, range 2–17 years) at a median time of 8 weeks after SARS-CoV-2 infection ( 46 ). Our results differ, however, from the study of Dailey et al who reported lower titers of anti-SARS-CoV-2 S-RBD antibodies in pediatric and young adult IBD patients ( n = 44, median age 18 years, range 11–26 years) in comparison to a control group of non-IBD children and adults ( 47 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in agreement with the observation that immunocompromised adult IBD patients with COVID-19 can develop a serologic response comparable to that of age-matched healthy controls ( 45 ). They are also in line with a recent study reporting a high rate of seroconversion (85%) in immunocompromised PIBD patients ( n = 12, median age 10 years, range 2–17 years) at a median time of 8 weeks after SARS-CoV-2 infection ( 46 ). Our results differ, however, from the study of Dailey et al who reported lower titers of anti-SARS-CoV-2 S-RBD antibodies in pediatric and young adult IBD patients ( n = 44, median age 18 years, range 11–26 years) in comparison to a control group of non-IBD children and adults ( 47 ).…”
Section: Discussionsupporting
confidence: 91%
“…Despite being a small monocentric study, the present work has several strengths. To the best of our knowledge, this is one of the very few studies investigating the immunological response to SARS-CoV-2 and the impact of COVID-19 on IBD course in pediatric IBD patients ( 46 , 47 ). Only subjects satisfying the WHO case definition of confirmed SARS-CoV-2 infection were enrolled in the study (both in the patient and in the control group).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that full vaccination of two or three doses of RNA vaccine can significantly increase the level of neutralizing antibodies in the recipients, preventing the occurrence of a global pandemic amid the frequent emergence of new variants of SARS-CoV-2 both in adults and children [45] , [48] , [108] , [109] , [110] , [111] , [112] , [113] . Robust clinical data also confirmed that the COVID-19 vaccine is safe in children with specific diseases, including congenital immunodeficiency, congenital heart disease, pediatric inflammatory bowel disease and allergy [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] . Given that some parents are still hesitant about vaccine safety, reducing the single-dose volume of vaccines for children and extending the vaccination interval has been proven to reduce the occurrence of adverse events, which is expected to become the vaccination strategy for children in the future [111] , [123] , [124] .…”
Section: Why Children Should Be Vaccinated Against Covid-19?mentioning
confidence: 74%
“…Some studies seem to indicate that IBD pediatric patients are generally able to develop a significant humoral immune response against SARS-CoV-2 and that in most of the cases this is quite similar to that detected in healthy individuals of the same age, regardless of disease activity and immunosuppressive therapy. In the study by Ruan et al seroconversion was tested in 12 subjects aged 2-17 years treated with various immunosuppressive drugs between 2.1 and 18.9 weeks (median 8.1 weeks) after initial positive SARS-CoV-2 PCR (53). The IgG antibody against the RBD of the S protein was detected in 10 (83.3%) children.…”
Section: Obesitymentioning
confidence: 99%
“…In the study by Ruan et al. seroconversion was tested in 12 subjects aged 2-17 years treated with various immunosuppressive drugs between 2.1 and 18.9 weeks (median 8.1 weeks) after initial positive SARS-CoV-2 PCR ( 53 ). The IgG antibody against the RBD of the S protein was detected in 10 (83.3%) children.…”
Section: Immune Response Of Patients With Inflammatory Bowel Disease ...mentioning
confidence: 99%